(untitled) (Bangladesh Journal of Medicine, 2023)
Naphthalene poisoning is a rare form of toxicity that may occur after ingestion, inhalation, or dermal exposure to naphthalene-containing compounds. It is a volatile polycyclic hydrocarbon used as a household deodorizer and moth repellent.Ingestional naphthalene poisoning can leadto methaemo-globulinaemia and intravascular haemolysis with diagnostic and therapeutic challenge. Associated G6PD deficiency may make it more complicated. A 20-year-old man presented with low-grade fever, lethargy and dark urine for 4 days.His vitals showed normal temperature, tachycardia with normal blood pressure and low oxygen saturation(76%) despite having high flow oxygen (15L/min).On repeated queries, he gave a history of ingesting a few naphthalene balls after a heated conversation with his friends. Laboratory workup showed features of haemolysis, methaemoglobinaemia, haemoglobinuria and low glucose 6 phosphate dehydrogenase level. The patient was treated conservatively with intravenous fluid, packed red blood cells transfusion, N acetylcysteine andascorbic acid with full recovery. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 218